Introduction to actuarial and financial mathematical methods - Garrett, Stephen J. (Academic Press is an imprint of Elsevier, 2015)
This self-contained module for independent study covers the subjects most often needed by non-mathematics graduates, such as fundamental calculus, linear algebra, probability, and basic numerical methods. The easily-understandable text of "Introduction to Actuarial and Mathematical Methods" features examples, motivations, and lots of practice from a large number of end-of-chapter questions. Questions range from short calculations to large project-based assignments, all designed to promote independent thinking and the application of mathematical ideas. Model solutions are included. The intuitive organization of "Introduction to Actuarial and Mathematical Methods" maximizes its usefulness as a means of self-study and as a reference source. Financial concepts and terminology introduce every mathematical concept and theory. For readers with diverse backgrounds entering programs of the Institute and Faculty of Actuaries, the Society of Actuaries, and the CFA Institute, "Introduction to Actuarial and Mathematical Methods" can provide a consistency of mathematical knowledge from the outset.